Environmental benefits of green roof to the sustainable urban development: A review - Chow M.F.; Bakar M.F.A. (Springer, 2023)
Air quality; Atmospheric temperature; Building codes; Planning; Population statistics; Roofs; Runoff; Storm sewers; Storms; Sustainable development; Water management; Water pollution; City; Environmental benefits; Green roof; Storm-water managements; Urban; Development and applications; Heating and cooling loads; Sustainable urban development; Urban Heat Island Effects; Urban growth